(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article deals with the features of anthroponyms of a literary text. In the course of the study, as an illustration of the analysis of theoretical positions, the novel by Mario Puzo was used. As a result of the analysis, the structural features of the functioning of anthroponyms in the figurative system of the literary text were revealed.